Hawa Nafsu Tidak Wajar Laki Laki dan Perempuan: Perbandingan Antara Surat Seneca 95 dan Surat Paulus di Roma 1:26-27 - Harold Pardede (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
The Apostle Paul's writings in Romans 1:26-27 explain unnatural sexual relations between men and women. This text is generally translated as the practice of same-sex (homosexual) relations. But long before the writings of the Apostle Paul there was a letter from the famous Stoic, Seneca, which discussed the background to the practice of same-sex relationships among the Romans. The text in Seneca's letter does not directly refer to Homosexual practices as traditionally understood in Paul's writings in Romans 1:26-27. This research aims to compare Seneca's letter 95 with Paul's writing in Romans 1:26-27. It aims to provide a different perspective on homosexuals and can provide historical background in Roman culture to Paul's writings in Romans 1:26-27. The research method in this research is hermeneutics and literature review. According to Romans 1:26-27, homosexual practices are a sin that incurs God's wrath. Meanwhile, for Seneca in letter 95, engaging in same-sex relations in Roman culture was motivated by a loss of wisdom, lack of self-control and the destruction of the morals of men and women, thus creating unnatural relationships.